PEMBENTUKAN BUDI PEKERTI DI TAMAN KANAK-KANAK VIDYA DHARMA KABUPATEN SEMARANG - Ratana, Veni; Sukodoyo, Sukodoyo; Dewi, Sukhitta (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2020)
This research aims to determine the formation of ethics in Vidya Dharma kindergarten in Semarang district. This research uses qualitative descriptive methods. The subjects of this research are administrators, kindergarten headmaster, teachers, and parents in the Vidya Dharma kindergarten. The techniques and the data collection used are observation, interviews, and documentation. While the data collection instruments usedare interview guidelines, observation guidelines, and camera or recording equipment. The ways to guarantee the validity of data obtainedare through continuous observation, triangulation, member check, transferability, dependability, and confirmability. The data obtained is analyzed using the Miles and Huberman method which includes data collection, data reduction, data display, and conclusion or verifying. The results of this study include three things, namely: (1) The forms of ethics performed by children, namely cooperation, responsibility, patience, discipline, courtesy, willingness to share, hygiene care, and self-reliance; (2) How to cultivate the ethics done by teachers by the teachers example and instruction; (3) The impact of ethical formation of child ethics is able to implement cooperation, responsibility, patience, discipline, courtesy, willingness to share, hygiene care, and self-reliance in the home and community environment.